Association between the Composite Dietary Antioxidant Index and severe headache or migraine: results from the National Health and Nutrition Examination Survey - Zhang, Zhiru; Chen, Xushan; Fang, Haotao; Ye, Jiechao; Tang, Xiaona; Huang, Rucheng (Frontiers in Neurology, 2024)
Background Severe headache or migraine is a neurological disease that seriously affects the quality of human life. Oxidative stress is considered a main factor in the pathogenesis of severe headache or migraine. The Composite Dietary Antioxidant Index (CDAI) is a score calculated using six dietary antioxidant components (including vitamins A, C, E, selenium, zinc, and carotenoid), which represents a person’s level of dietary antioxidant ingredients. Based on the theory of oxidative stress, we speculated that CDAIs may be relevant to the risk of severe headache or migraine, as the relationship between the CDAI and severe headache or migraine is unclear. Hence, the purpose of this study was to explore the relationship between the CDAI and severe headache or migraine in participants. Methods We performed a cross-sectional study using data from the National Health and Nutrition Examination Survey (NHANES) that were collected from 2001 to 2004. A total of 4,943 participants were included, of whom 1,232 experienced severe headaches or migraines. Participants’ CDAIs were calculated based on their intake of six dietary antioxidants. We used logistic regression models, limited cubic spline analysis, and subgroup analysis to assess the association of CDAI with severe headache or migraine. Results The multivariate logistic regression model (correcting for all potential covariates) revealed that the odds ratio (95% Confidence Interval [CI]) for the association between CDAI and severe headache or migraine was 0.97 (95% CI = 0.95–1.00, p = 0.048). Compared with individuals with low CDAIs in Quartile (Q)1, the adjusted Odds Ratio between the CDAI and severe headache or migraine in Q2, Q3, and Q4 were 0.84 (95% CI = 0.69–1.01, p = 0.07), 0.77 (95% CI = 0.63–0.96, p = 0.017), and 0.73 (95% CI = 0.56–0.95, p = 0.02), respectively. Restricted cubic spline regression analysis showed an L-shaped relationship between the CDAI and severe headache or migraine. Conclusion Our findings indicate that higher CDAI was associated with a lower risk of severe headache or migraine.